2016
DOI: 10.1161/strokeaha.115.011086
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Histology Verified Intracranial Atherosclerotic Disease by 1.5T Magnetic Resonance Imaging

Abstract: Intracranial atherosclerotic disease (ICAD), as a most common cause of ischemic stroke, has been drawing increased attentions of clinicians and researchers in the worldwide. 1 Advanced imaging techniques, especially High Resolution Magnetic Resonance Imaging (HRMRI), could visualize the pathology of intracranial arterial diseases.2 However, current knowledge about histology of intracranial atherosclerosis lags behind the development of updated imaging modalities due to lacking of vessel specimens. Our previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
(12 reference statements)
1
17
1
Order By: Relevance
“…For intracranial vascular disease, eccentric wall thickening has been used to distinguish intracranial atherosclerosis from other etiologies1819. A recent in vitro study showed that eccentric plaques were associated with a non-significant higher risk of cerebrovascular events compared with concentric plaques (30.77% vs. 17.39%; n = 72, P = 0.241)5. Our study showed that symptomatic plaques were associated with a significantly higher eccentricity index than asymptomatic plaques after adjusting for the plaque burden (P = 0.028).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For intracranial vascular disease, eccentric wall thickening has been used to distinguish intracranial atherosclerosis from other etiologies1819. A recent in vitro study showed that eccentric plaques were associated with a non-significant higher risk of cerebrovascular events compared with concentric plaques (30.77% vs. 17.39%; n = 72, P = 0.241)5. Our study showed that symptomatic plaques were associated with a significantly higher eccentricity index than asymptomatic plaques after adjusting for the plaque burden (P = 0.028).…”
Section: Discussionmentioning
confidence: 99%
“…The eccentricity index was defined as follows: (maximum wall thickness−minimum wall thickness)/maximum wall thickness (Fig. 1)5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,7,8 Recent study 8 17.39%, p=0.241). 42 Retrospective high resolution MR study including non-significant stenosis in the intracranial vessel demonstrated that eccentricity was more higher in the symptomatic plaque than in the asymptomatic plaque (p=0.028). 45 Another study including symptomatic significant MCA stenosis showed that plaques with non-significant luminal narrowing was associated with eccentricity (p<0.05).…”
Section: Assessment Of Carotid Plaque Burden Using Ultrasonographymentioning
confidence: 95%
“…Progress in imaging technology such as high-resolution magnetic resonance imaging (MRI) has enabled the visualization of arterial morphological changes in ICAS,[1243] and as reported in the coronary and other systemic arteries,[347182031323839] cerebral atherosclerotic lesions are known to exhibit considerable heterogeneity in morphological structures. Several arterial remodeling patterns, such as the “positive/negative” remodeling pattern, which is defined by the presence of outward expansion of the outer diameter, and the “eccentric/concentric” remodeling pattern, which is defined by the eccentricity of the wall morphology, have been reported previously.…”
Section: Introductionmentioning
confidence: 99%